صوفیاء کرام ؒکے افکار کا امام شعرانی کی تعلیمات کی روشنی میں جائزہ : Review of Sufi Thoughts in the light of Imam Abdul Wahab Sherani’s Preaching - Dr. Abdul Majeed Baghdadi,; Rehmat Bao g, (MEI, 2023)
The religious scholars who were a symbol of guidance to the people, who brought the light of Islam to this world, are many and amongst them distinguished is Imam Abdul Wahab Al Sherani. Imam Abdul Wahab Al Sherani is a scholar who wrote books on different sciences, he was a Sufi, and he wrote more than 300 books; no doubt that he was a big Sufi Scholar. In this Article with the recognition of his services, I will explore about his beliefs and theories. It is a critical study on his Beliefs and Theories. Abdul Wahab Sherani is such a person he is not only a Sufi, but also a renowned scholar of his age, we can find in his teachings a complete message of his beliefs and theories .He is not only known in Pakistan alone but is also recognized as an authority all over the world as a Sufi Muslim.